2022
DOI: 10.35848/1347-4065/ac9103
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of defect states in light-irradiated single-crystal ZnO by low-temperature positron annihilation lifetime spectroscopy

Abstract: Positron annihilation lifetime spectroscopy of single crystalline ZnO during light illumination has been performed in conjunction with electron spin resonance (ESR) to investigate defects related to persistent photoconductivity. The intensity of the ESR signal changes depending on light wavelengths and the apparent positron lifetime during red-light illumination is approximately 6 ps lower on average than that during blue-light illumination. The results suggest that the excitation of VO during blue-light illum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In our previous study, it was reported that under red light irradiation at liquid nitrogen (LN 2 ) temperature, the apparent positron lifetime of single-crystal ZnO was, on average, approximately 6 ps lower compared to that under blue light irradiation. 3) This results indicate that the presence of positively charged oxygen-vacancy (V O ) increases during blue light irradiation (excitation) and decreases during red light irradiation (relaxation), leading to a decrease in the apparent positron lifetime. These observed behaviors of vacancies are closely related to the phenomenon of persistent photoconductivity (PPC) in ZnO.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…In our previous study, it was reported that under red light irradiation at liquid nitrogen (LN 2 ) temperature, the apparent positron lifetime of single-crystal ZnO was, on average, approximately 6 ps lower compared to that under blue light irradiation. 3) This results indicate that the presence of positively charged oxygen-vacancy (V O ) increases during blue light irradiation (excitation) and decreases during red light irradiation (relaxation), leading to a decrease in the apparent positron lifetime. These observed behaviors of vacancies are closely related to the phenomenon of persistent photoconductivity (PPC) in ZnO.…”
mentioning
confidence: 85%
“…Previous studies have indicated that red light irradiation reduces the apparent positron lifetime, suggesting an increase in the number of neutral oxygen vacancies. 3) If positrons are captured by V O , the number of positrons annihilated with Zn electrons would increase, resulting in a spectrum approaching the Zn spectrum (i.e. an increase around 20 × 10 −3 m 0 c in Fig.…”
mentioning
confidence: 99%